Knowledge Sharing as a Double-Edged Moderation in Enhancing Employee Digital Performance through Proactive Personality and Organizational Learning - Khairunnisah, Wahyuni; Anjaningrum, Widiya Dewi; Fernandez, Khriz N. (APMBA (Asia Pacific Management and Business Application), 2025)
Anchored in the resource-based view (RBV) and dynamic capability theory (DCT), this study examines how Proactive Personality and Organizational Learning (OL) influence Employee Digital Performance (EDP) through Employee Dynamic Capability (EDC) as a mediator and knowledge sharing (KS) as a moderator. Using a quantitative approach with data from 310 craft-based MSME respondents in East Java and analysed via PLS-SEM, the results indicate that Proactive Personality and Organizational Learning positively affect Employee Digital Performance, both directly and indirectly through Employee Dynamic Capability. Knowledge Sharing strengthens the Proactive Personality – Employee Digital Performance link but slightly weakens the Organizational Learning – Employee Digital Performance relationship when overly formal. These findings confirm that Proactive Personality and Organizational Learning are strategic resources that build dynamic capabilities, enhancing MSMEs’ adaptability and digital competitiveness. Managers should balance structured learning with flexible knowledge sharing to sustain innovation. Future research could examine organizational culture, transformational leadership, and technology support, while qualitative studies may clarify how social and cultural interactions influence Knowledge Sharing in enhancing employee digital performance.